2006
DOI: 10.1124/jpet.106.112474
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Norepinephrine Release in Hypothalamic Paraventricular Nucleus and Amygdala Is Mediated by N-Methyl-d-aspartate Receptors and Nitric Oxide in the Nucleus Tractus Solitarius

Abstract: The noradrenergic projections from brainstem nucleus tractus solitarius (NTS) to hypothalamic paraventricular nucleus (PVN) and amygdala (AMYG) are involved in nicotine-related stress responses and drug craving. Previous studies demonstrated that i.v. nicotine-induced norepinephrine (NE) release in the PVN and AMYG depends on nicotinic cholinergic receptors in the brainstem. However, the direct site and mechanism of nicotine's action in brainstem are unknown. The present study determined the roles of NTS ionot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
(53 reference statements)
1
35
2
Order By: Relevance
“…We further demonstrated that nicotine indirectly induces ACTH secretion from the anterior pituitary by directly activating noradrenergic areas of the nucleus tractus solitarius (Matta et al, 1998;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We further demonstrated that nicotine indirectly induces ACTH secretion from the anterior pituitary by directly activating noradrenergic areas of the nucleus tractus solitarius (Matta et al, 1998;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 66%
“…Corticotropin-releasing factor (CRF) neurons in the hypothalamic paraventricular nucleus (PVN), which are pivotal regulators of ACTH secretion, are not directly activated by nicotine (Matta et al, 1987). Instead, nicotine indirectly activates PVN CRF neurons (Matta et al, 1990) by stimulating a cascade of neurotransmitters in the nucleus tractus solitarius (NTS) that activate noradrenergic projections to the PVN (Zhao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, acute injection of nicotine, the principal psychoactive component of tobacco smoke, is a potent stimulus for secretion of the stress-responsive hypothalamo-pituitary-adrenal (HPA) axis hormones ACTH (Conte-Devolx et al, 1981;Cam and Bassett, 1983;Matta et al, 1987) and corticosterone (Balfour et al, 1975;Cam and Bassett, 1983). Acutely injected nicotine increased glutamate release and enhanced NMDA receptor activity in noradrenergic regions of the nucleus tractus solitarius projecting to the hypothalamic paraventricular nucleus (PVN) (Zhao et al, 2007), projections shown to stimulate norepinephrine release and activate corticotropin-releasing factor (CRF) neurons in PVN (Valentine et al, 1996;Matta et al, 1998). However, the effect of chronically self-administered nicotine on these stress-responsive systems has not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the reduced level of dopamine in the nucleus accumbens recovers the animal's ability to acquire used to stress following inescapable stress (Dubrovsky, 2005;Viveros et al, 2007;Colomer and Olivos-Oré et al, 2010;Hunter and Bloss et al, 2010). Various parts of reward system are involved in the variation of stress responses and the nucleus accumbens as a main parts of this reward system, acting a vital role in inhibiting the effects of stress (Zhao et al, 2007). In the present study, the stimulation of nicotinic receptors in the nucleus accumbens induced different responses indicating the influence of the cholinergic system in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 68%